Development of Professional Learning Communities Model to Improve Digital Pedagogy Skills of Elementary School Teachers in Science Learning: Effectiveness Test - Rintayati, Peduk (Journal of Elementary School Education, 2023)
Science learning in the 21st century requires teachers who are skilled at integrating technology functions into interactive science learning by utilizing multimedia to support students' scientific mastery of science concepts. However, the digital pedagogical skills of primary school teachers are still weak. This study aims to determine the effectiveness of the professional learning communities (PLC) model developed to improve the digital pedagogy skills of elementary school teachers in science learning. This research is research and development at the stage of operational field testing. The study applied the pretest posttest control group design method. The research data was collected through tests of teachers' digital pedagogical skills in terms of learning tools. The research sample was 52 elementary school teachers in Surakarta City. The results of the study obtained a sig score. (2-tailed) of 0.002 <0.05 so it was concluded that the digital pedagogy skills of teachers in the experimental group were better than the control group. It can be concluded that the developed PLC model has been effective in improving the digital pedagogy skills of elementary school teachers in learning science.